Two new spider species of the genus Conculus (Araneae, Anapidae) from Southeast Asia - Zhang, Qiqi; Lin, Yucheng (Zootaxa, 2019)
Two new species the spider family Anapidae are described from Southeast Asia: Conculus sagadaensis n. sp. from Philippines and Conculus yaoi n. sp. from Indonesia, both described after male specimens. Conculus is reported from Southeast Asia for the first time. Diagnoses and illustrations are provided for two new species. The types are deposited in the Natural History Museum of Sichuan University (NHMSU) in Chengdu, China.